ANALISIS DESKRIPTIF : INTEGRASI MEDIA PEMBELAJARAN KONTEKSTUAL ‘KANTIN SPLDV’ MELALUI PENDEKATAN DEEP LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP - Hasibuan, Adinda Muhfyana; Qoyyima, Annisa; Ajarah, Desi; Sitorus, Cellion Lydia Magdalena; Manurung, Pera Novia; Siregar, Budi Halomoan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The background of this research problem is the low conceptual understanding of students in the Two-Variable Linear Equation System (SPLDV) material. This problem is identified as being rooted in the abstract nature of the material and the limited availability of learning media relevant to real life. This study focuses on analyzing the effectiveness of integrating contextual learning media called